Wittgenstein’s Relevance to Philosophy of Education: personal reflections on meaningful uses of post-foundationalism - Jeff Stickney (Educação & Realidade, 2020)
Invited to survey my work in Philosophy of Education related to the later philosophy of Ludwig Wittgenstein, I first investigate how Wittgenstein became a significant thinker in this field. Affirming this connection after some deflationary remarks, clarifying the philosophical as opposed to pedagogical intent of Wittgenstein’s frequent remarks on learning, I then revisit my contest with Michael Luntley over interpreting Wittgenstein’s remarks on training. Eliding the Abrichtung, ‘animal-training’ reading, I side with José Medina’s social-normative view of gradually attaining (through training), autonomy within and mastery of the rules. Following the widely shared social-normative reading then opens a vista onto several meaningful applications in education of Wittgenstein’s post-foundational philosophy. One case is rule-deviation within curriculum reforms, where instead of standardization and consensus we find multiple interpretations of curricular rules. Another vexing question is how we judge with some degree of certainty the efficacy or sanity of various pedagogical practices, as in weighing the merits of discovery versus fundamentals approaches in math training. Recognizing how people become potentially blinded by long-held, second-nature reactions and ‘bedrock’ assumptions, and drawing also on Foucault, I consider applications to social justice issues in terms of how we commonly regard others: diagnosing students as ADHD or Gifted, calling out abusive language in schools, recognizing Indigenous claims for sovereignty in a process of decolonizing education, and seeing trees and other non-human beings as something more than standing resources.